Combination of geophysical and soil mapping methods related to reforestations in semi-arid regions - Mannschatz, Theresa; Feger, Karl-Heinz; Dietrich, Peter (Águas Subterrâneas, 2011)
This study analysis the influences of reforestation measures on soil properties and water balance in semi-arid areas such as Northeastern Brazil. For an improved hydrological modeling innovative combinations of geophysical, remote sensing and digital soil mapping methods for the assessment of needed soil parameters will be applied.